ANALISIS PEMASARAN DAN STRATEGI PENGEMBANGAN USAHA NILAM (Pogostemon Cablin Bentha) DI KABUPATEN KONAWE SELATAN - Qomariah, Erni; Purwanti, Rahayu Endah; Fachruddin, Sutiyana; Ramalan, La Ode (Jurnal Ilmiah Penyuluhan dan Pengembangan Masyarakat, 2023)
The problem often faced by patchouli farmers is in the marketing process of their products. In general, when marketing patchouli in South Konawe Regency, farmers collaborate through marketing institutions or intermediary traders to market their products. Basically, the high marketing costs cause many farmers to depend on marketing institutions that are able to provide facilities such as transportation and the needs that farmers need to market their products. The aim of this research is to determine and analyze marketing channels, differences in share margins, and marketing efficiency of patchouli plants in South Konawe Regency. The research design used was descriptive quantitative. The respondents for this research consisted of patchouli farmers and traders. The sampling technique was carried out using purposive sampling technique. The data analysis used is calculating the share margin, margin and marketing efficiency. Then descriptive qualitative data analysis was used using SWOT analysis. The research results show that the marketing channels for patchouli oil that have been formed are: Patchouli Farmers to Small Traders to Large Traders to Consumers (Industry). The calculation results show that the Share Margin value is 61.03%, meaning that the determination of the selling price made by farmers is included in the efficient category. It is said to be efficient if the farmer's selling price is more than or equal to 40% of the purchase price at the exporter level. The marketing efficiency value is 15.59%. The smaller efficiency value indicates that the use of existing marketing channels in the research area can be said to be more efficient because of the lower ratio of total marketing costs to selling prices to final consumers. The strategies that need to be implemented are maximizing the productivity of patchouli farming, increasing farmers' knowledge and education, production facilities and infrastructure as well as increasing cultivation and post-harvest technology facilities, utilizing the level of productivity of patchouli as an export crop to earn more income, taking advantage of the large number of productive farmers who are still farming. patchouli, controlling prices from the government so that there are no price games, increasing education, knowledge and experience and skills of farmers in applying cultivation technology, and increasing the number of technological facilities for processing products to meet quality standards set by traders/industry and also be able to reduce the risks that arise due to fluctuating price competition.